Comparative Study of Productive Traits and External Morphological Characteristics of Endemic Indigenous Chickens in Polewali Mandar within the Framework of Poultry Science - Lilis Ambarwati; Fajrun Najah Ramhan; Kurnia Kurnia; Sri Muharmita; Faharia Arif (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
This study aims to map and record the external morphological characteristics and production traits of endemic local chickens distributed across three subdistricts in Polewali Mandar Regency, namely Tapango, Bulo, and Matakali. The research method used is descriptive qualitative and quantitative. The quantitative characteristics observed included body weight, body length, chest circumference, wingspan, tail feather length, and wing feather length, while the qualitative characteristics included chest feather color, comb color, wattle color, and shank color. The sample consisted of 40 males aged >20 weeks in each subdistrict. The results of this study show that endemic local chickens have the highest body weight in Matakali District (1.07±0.13 kg) with a Coefficient of Variation of 12.17%, the highest body length in Tapango District (19.60±1.44 cm) with a Coefficient of Variation of 7.37%, the highest chest circumference in Matakali Subdistrict (33.34±2.24 cm) with a Diversity Coefficient of 6.72%, the highest wingspan in Tapango Subdistrict (27.45±1.52 cm) with a Diversity Coefficient of 5.53%, the longest tail feathers in Tapango (4.65±2.11 cm) with a coefficient of variation of 26.13%, the longest wing feathers in Matakali District (16.31±1.18 cm) with a coefficient of variation of 11.11%. The qualitative characteristics of endemic local chickens showed 100% black breast feathers in all subdistricts, 60% bright red combs in Tapango, and 55% in Bulo and Matakali. The dominant comb color was bright red in 60% of chickens in Tapango, 55% in Bulo, and 50% in Matakali. Shank color